Comprehensive Guidance: Internalization of Transformative Islamic Values (Case Study at SMP Muhammadiyah Al-Kautsar Special Program, Gumpang) - Istanto Istanto; In Taslimah (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2017)
This study revealed the implementation of the Comprehensive Guidance program in inculcating the character values in the students of SMP Muhammadiyah Al-Kautsar Special Program in academic year 2016/2017. The purpose of this study was to find out the character values promoted in the program. It is a field research using the methods of in-depth interview, observation and documentation. The findings conclude that Comprehensive Guidance is thorough guidance or counseling for students that includes several programs of Upgrading Motivation, Character Building, Spiritual Guidance, Academic Coaching, Counseling Program, Home Visit, Mentoring, Out Door Program, and Holistic Monitoring. The implementation of Comprehensive Guidance program can instill the values of transformative Islam, such as religious, honest, discipline, creative, independent, enthusiast, patriotic, friendship, caring, and responsible.